What do we really know about fiscal sustainability in the EU?: a panel data diagnostic - António Afonso; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2008)
We assess the sustainability of public finances in the EU15 using stationarity and cointegration analysis. Specifically, we use panel unit root tests of the first and second generation allowing in some cases for structural breaks. We also apply modern panel cointegration techniques developed by Pedroni (1999, 2004), generalized by Banerjee and Carrion-i-Silvestre (2006) and Westerlund and Edgerton (2007), to a structural long-run equation between general government expenditures and revenues. While sustainability may be lacking in individual cases, fiscal policy was overall sustainable both for the EU15 panel set, and within some sub-periods.
Keywords: C23; E62; H62; H63; 330; intertemporal budget constraint; fiscal sustainability; EU; panel unit root; panel cointegration; Finanzpolitik; Budgetrestriktion; Verschuldungsrestriktion; EU-Stabilitätspakt; Geldpolitik; Europäische Wirtschafts- und Währungsunion; EU-Staaten